2016
DOI: 10.4236/ajps.2016.716206
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Improvement of a Bioherbicidal Fungus Using a Formulation-Based Approach

Abstract: Greenhouse experiments were conducted to determine the effects of an invert (water-in-oil) emulsion (IE) on dew period duration and dew delay of Colletotrichum coccodes for biocontrol of the problematic weed, eastern black nightshade (Solanum ptycanthum). Dew periods of 4, 8, or 12 h provided 10%, 25%, and 40% control of eastern black nightshade plants, respectively, when C. coccodes (Strain NRRL 15,547) spores were applied in water + Tween 80 surfactant 12 days after inoculation, but a minimum of 16 h of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…are of particular interest. A number of studies are aimed at studying the possibility of using micromycetes as herbicides [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…are of particular interest. A number of studies are aimed at studying the possibility of using micromycetes as herbicides [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the endophytes' role in the formation of plants' resistance to metals, including crops (Rodriguez et al, 2009;Ikram et al, 2018;Bilal et al, 2019;Dabral et al, 2019;El-Samad et al, 2019), and with regard to chemical elements that are extremely dangerous for plants (Ali et al 2019;Bilal et al, 2020;Li et al, 2019;Sharma et al, 2019;Hou et al, 2020) are of particular interest. A number of studies are aimed at examining the possibility of using micromycetes as herbicides (Sogonov & Velikanov, 2004;Boyette et al, 2016;Boyette et al, 2018;Meepagala et al, 2019;Sobowale, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The development of this technology includes the optimization of the nutrient medium for the viability and aggressiveness of the material [16]. For phytopathogenic micromycetes, it is shown that the aggressiveness of infectious material is determined by the nature of carbon and nitrogen sources, their ratio and absolute concentration [19][20][21], as well as the physiological state of propagules [6]. It is necessary to note that for phomoid micromycetes, which include S. cirsii, the comprehensive study to assess the impact of the cultivation duration, the nature, and concentration of carbon and nitrogen sources on the quality of the mycelium, obtained in the result of deep fermentation, has not been carried out.…”
Section: Introductionmentioning
confidence: 99%